FASIES KUARTER VULKANIK DAERAH PAGAR JATI DAN SEKITARNYA, KAB.BENGKULU TENGAH, BENGKULU - Aditya N.P.H; Oke Aflatun; Idarwati Idarwati (Komunikasi Fisika Indonesia, 2018)
The Jati Fence Area, Bengkulu is the fore arc basin area whose deposition is influenced by the volcanic event. The deposition event took place on a quaternary volcano that has been active in having sedimentation activities that continue. This study aims to carry out mineralogical analysis in the proximal facies deposit area with petrographic data at observation locations (LP) 14, 59, 81,108, and (ST) 14,70 which are sourced from the results of local geological mapping. In LP 81 and 14 with proximal facies have volcanic breccia lithology with compilation components which are dominated by andesitic rocks, pyroclastic matrix composition, packed packing, hard hardness, and mineralogicalcomposition which tend to have many crystals. In LP 59 and 108 proximal facies found andesite lava.